Geological characterization of the Aquistore CO2 storage site from 3D seismic data. (November 2016) - White, D.J.; Hawkes, C.D.; Rostron, B.J.
Highlights: Geological characterization of 120 km 3 volume at Aquistore CO2 storage site. Regional evaporite seal is continuous and >150 m thick. Reservoir caprock is continuous. Absence of through-going vertical faults. Basement fault orientation likely precludes reactivation. Abstract: A 30 km 2 3D seismic survey was conducted in 2012 at the Aquistore CO2 storage site near Estevan, Saskatchewan, Canada. The purpose of the survey was to investigate the geological suitability of this site for the purposes of long-term CO2 storage. The resultant 3D seismic volume has been interpreted in conjunction with geological and geophysical logs from the 3400 m deep CO2 injection well (01/5-6-2-8-W2M) that was subsequently drilled. The CO2 storage reservoir resides immediately above the Precambrian crystalline basement (3400 m) and is part of a regionally extensive >200 m-thick clastic interval (Winnipeg and Deadwood formations). The reservoir is capped by a 15 m thick laterally-continuous shale unit (Icebox Member of the Winnipeg Formation). A regional evaporite at ∼2500 m depth (Prairie Formation) provides a secondary barrier to vertical flow. It is >150 m thick and shows no salt dissolution features. Above the Prairie Formation are 1500 m of laterally continuous Middle Devonian to Lower Cretaceous strata and 1000 m of Upper Cretaceous and younger sedimentary rocks, including additional regionally-extensive aquitards that provide tertiary seals: Watrous Formation (∼120 m), Colorado Group (>185 m), and Bearpaw Formation. There is no evidence of vertical faulting extending through the Devonian or deeper section. A local sub-vertical Precambrian basement fault is interpreted to exist. It lies beneath a flexure within the overlying Cambrian to Silurian strata. The fault is oriented at an azimuth of 75°–85° relative to the regional maximum horizontal stress making it less susceptible to reactivation during CO2 injection. There is no clear evidence that the strata in an overlying flexure are ruptured or faulted. Natural seismicity in the area is very low and the nearest known significant seismogenic fault zone is located ∼200 km away.